Hemospray for recurrent esophageal band ulcer bleeding - Sanglodkar, Uday A.; Jothimani, Dinesh; Rela, Mohamed (Clinical and Experimental Hepatology, 2018)
Rebleeding after initially successful endoscopic variceal ligation (EVL) occurs in 20-60% of patients, most commonly from band ulcers, and is associated with 20-50% mortality. Although band ulcer bleeding has been treated in a number of different ways, no single therapeutic intervention has shown a clear benefit. Hemospray (Cook Medical, Winston-Salem, North Carolina, USA) is a relatively new non-contact hemostatic modality used in the management of bleeding peptic ulcers. It is a nano-powder that can be sprayed over a larger mucosal area. Here we describe a patient with end stage liver disease who presented with recurrent bleeding from a deep esophageal ulcer following band ligation and sclerotherapy, effectively managed with multiple sessions of Hemospray.